Renovascular Hypertension in Chronic Hemodialytic Patient - Lestari, Sri; Prasanto, Heru; Kuswadi, Iri (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: Hypertension is a major contributor to the development of chronic kidney disease. Data in Indonesia, hypertension is still the most comorbid disease in CKD patients on dialysis (51%). Hypertension in CKD on dialysis patients is common and often uncontrolled. Renovascular hypertension is the most common cause of secondary hypertension. Diagnosis and treatment of RAS is very important, because it can accelerate the achievement of blood pressure targets, reduce the risk and complications due to hypertension. Case Report: A 52-year-old woman with CKD has been undergoing hemodialysis for 2 years. Hypertension that was previously well controlled for 2 years required an increase in antihypertensive therapy from 2 to 4 drugs in recent months. On physical examination the blood pressure 180/90 mmHg, pulse 79 bpm, respiration 20/min, temperature 36.7oC. Conjunctiva looks anemic, cardiomegaly, lungs within normal limits, no ascites and edema in the extremities. On renal artery duplex ultrasound examination, right main renal artery acceleration time 147.65 ms, Peak Systolic Velocity (PSV) 31.9 cm/s. RI 0.69 and left main renal artery acceleration time 120.81 ms, PSV 16.9 cm/s, RI 0.61. There was 20-30% left renal artery stenosis, 80% right renal artery stenosis. A stent was placed on the right renal artery. The patient’s condition after PTRA improved, but at the next follow-up, mean systole and diastole 170 mmHg and 80 mmHg, respectively. Patient received 4 antihypertensive therapy. Conclusion: Renal artery stenosis is a disease that consists of a broad spectrum of different entities with different pathophysiologies that require varied approaches to diagnose and treat. Current diagnostic tools include MRA, CTA and renal artery duplex ultrasonography. Patients with renal parenchymal disease are poorer candidates for revascularization.